Farewell My Concubine: Operatic Film as a Political Allegory - Loska, Krzysztof (Media - Culture - Social Communication, 2020)
The starting point of the presented deliberations is the concept of political allegory in the work of Ann W. Astell. This researcher assumes that the basic element in creating a political allegory is to establish an agreement between an author and a recipient, or the presence of shared knowledge and cultural memory allowing the signs encoded in the text to be read. The aims of the present interpretation of Farewell My Concubine by Chen Kaige are, firstly, to show the relationship between personal and collective trauma and, secondly, to analyse how historical events and figures are integrated in a fictional story about two actors of the Beijing Opera. Finally, the interpretation focuses on the functioning of a film as an allegory.